Symbiotic nutrient cycling enables the long-term survival of Aiptasia in the absence of heterotrophic food sources - Rädecker, Nils; Meibom, Anders (Peer Community Journal)

(untitled)
Phototrophic Cnidaria are mixotrophic organisms that can complement their heterotrophic diet with nutrients assimilated by their algal endosymbionts. Metabolic models suggest that the translocation of photosynthates and their derivatives from the algae may be sufficient to cover the metabolic energy demands of the host. However, the importance of heterotrophy to the nutritional budget of these holobionts remains unclear. Here, we report on the long-term survival of the photosymbiotic anemone Aiptasia in the absence of heterotrophic food sources. Following one year of heterotrophic starvation, these anemones remained fully viable but showed an 85 % reduction in biomass compared to their regularly fed counterparts. This shrinking was accompanied by a reduction in host protein content and algal density, indicative of severe nitrogen limitation. Nonetheless, isotopic labeling experiments combined with NanoSIMS imaging revealed that the contribution of algal-derived nutrients to the host metabolism remained unaffected due to an increase in algal photosynthesis and more efficient carbon translocation. Taken together, our results suggest that, on a one- year timescale, heterotrophic feeding is not essential to fulfilling the energy requirements of the holobiont. But, while symbiotic nutrient cycling effectively retains carbon in the holobiont over long time scales, our data suggest that heterotrophic feeding is a critical source of nitrogen required for holobiont growth under oligotrophic conditions.